Impact of Human Intervention and Sea Level Rise on Water-Logging Scenarios inside Polders-24 And 25 of Bangladesh - Haider, Jamal M; Aminul, Haque M; Md Jahid, Hossain; Anisul, Haque (Journal of Engineering Science, 2022)
Coastal region of Bangladesh possesses a fragile ecosystem and is exposed to hazards like cyclones, floods, storm surges, and water-logging. A detail understanding on the impact of water-logging due to various natural, man-made and climate change scenarios is still lacking. Considering this research gap, the present research is aimed to study impacts of these scenarios inside polders-24 and 25 which are situated on the western part of the coastal region. In this Study as natural scenario, sedimentation in the Hari River; as man-made scenario, new polders in the south-central region and as SLR scenario, an extreme sea level rise of 1.48m are considered. Long-term satellite images are analyzed, and numerical model is applied in the study area. The result shows that water-logging is more acute inside polder-25 compared to polder-24. Sedimentation in Hari River aggravates the water-logging condition. Dredging in Hari River does improve the situation. Journal of Engineering Science 12(3), 2021, 73-83